Art hacking for business innovation: An exploratory case study on applied artistic strategies - Berit Sandberg (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Despite a growing interest in the effects of arts-based interventions on organizational change, concepts aiming at business innovation and product development other than residencies are rare. Furthermore, little is known about the role and impact of artists involved in idea-generating formats. How does the personal presence of artists in a heterogenous working group influence the procedure? To what extent do artists unfold their creative qualities while dealing with such a non-artistic challenge? The paper introduces a method named Art Hacking that applies professional labour attitudes typical for artists and artistic modes of thinking to business problems and enhances the approach by having artists attend the whole intervention. One of these events was taken as a case for exploring the role of four artists in the collective idea-generation process. The results of participatory observation along critical incident technique substantiate the thesis that in interdisciplinary "playgrounds" artists implicitly become process leaders. They are catalysts for awareness, sensemaking and change of perspective.
Keywords: 650; Art Hacking; Art Thinking; arts-based intervention; creative leadership; innovation; idea generation